Historical development of god consciousness and its implication on humanities and social science research methodology - Ahsan, Abdullahil (2015)
―In the beginning, human beings created a God who was the First Cause of all things and Ruler of heaven and earth.‖ Thus begins historian of religion Karen Armstrong her book A History of God: The 4000-Year Quest of Judaism, Christianity and Islam.1 This was a natural outcome of the Enlightenment methodology of finding historical truth. But do we really have reliable historical records from the earliest human inhabitance on this planet? Due to the lack of such information researchers have generally relied on myths and archaeological evidences for investigation on the subject. Armstrong says, ―A brief look at the Enuma Elish [creation myth of ancient Mesopotamia] gives us some insight into the spirituality which gave birth to our own Creator God centuries later. Even though the biblical and Koranic account of creation would ultimately take a very different form, these strange myths never entirely disappeared, but would reenter the history of God at a much later date, clothed in a monotheistic idiom.‖2 Armstrong, like sociologists, wants to understand religion from the beliefs of followers. Armstrong adopts this approach of understanding the phenomenon of God consciousness by means of contemporary social science methodology. Taking the queue from Armstrong’s research methodology this article examines the current state of research methodology in humanistic and social sciences about God consciousness and its implications in society.